Dental and skeletal characteristics of patients with biprotrusion. Narrative review - Munive Méndez , Arnaldo (2024)
Biprotrusion, defined as the protrusion of the incisors and labial prominence, requires a personalized clinical approach to address both oral functionality and facial aesthetics. Historically, treatment strategies have varied between extraction and non-extraction, highlighting the importance of accurate diagnosis to guide current therapeutic approaches. Therefore, the goal was to conduct a narrative review on the dental and skeletal characteristics of patients with biprotrusion. From a literature search, 352 articles were obtained from January 1, 2018, to February 29, 2024, with 8 selected based on selection criteria and availability. In conclusion, studies reveal discrepancies between Caucasian cephalometric norms and the dental and skeletal characteristics of Afro-Brazilian, Saudi, South African, and Indian populations, emphasizing the need to adapt orthodontic practices to ethnic diversity and to thoroughly review the aggravating characteristics of biprotrusion.